2021
DOI: 10.1093/gerona/glab013
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Light Physical Activity and Cognition Among Adults: A Scoping Review

Abstract: Background The physical and cognitive benefits of moderate-vigorous intensity physical activity (MVPA) for adults have been well documented. Recently, there has been increasing interest in the independent health benefits of light-intensity physical activity (LPA). This research has primarily focused on the relationship between LPA and morbidity and mortality risk, with few studies investigating cognitive associations. The purpose of this scoping review was to catalog existing evidence on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 131 publications
0
9
0
Order By: Relevance
“…However, there was no significant difference on cognition between the two resistance exercise groups, which suggests that moderate-intensity resistance exercise was as effective as high-intensity resistance exercise in improving cognition in older adults. Notably, previous research showed that light-intensity physical activity had positive effects on cognition [ 71 , 72 ], which implies that exercise interventions can be effective in improving or maintaining cognitive functioning even with light intensity.…”
Section: Discussionmentioning
confidence: 99%
“…However, there was no significant difference on cognition between the two resistance exercise groups, which suggests that moderate-intensity resistance exercise was as effective as high-intensity resistance exercise in improving cognition in older adults. Notably, previous research showed that light-intensity physical activity had positive effects on cognition [ 71 , 72 ], which implies that exercise interventions can be effective in improving or maintaining cognitive functioning even with light intensity.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between physical activity and executive function may be more prominent among older adults, 56 whereas the present sample included only young adults aged 39 years or younger. Light physical activity is connected to positive cognitive outcomes among adults, 57 suggesting that relatively small behavioral changes among CHD survivors may improve well-being. Older age and female sex were associated with insufficient physical activity, affirming previous findings 58 …”
Section: Discussionmentioning
confidence: 99%
“…The outcomes of physical activity and health education on cognition level in sedentary seniors findings suggest that light physical activity may benefit cognition across adulthood (8). Jannique et al performed a systematic review and metaanalysis including 23 RCT studies to evaluate the effect of exercise on older adults' cognition.…”
Section: Letter To Editormentioning
confidence: 99%